'Omics' approaches for studying the microbiome in Alopecia areata. (21st September 2020) - Pinto, Daniela; Trink, Anna; Sorbellini, Elisabetta; Giuliani, Giammaria; Rinaldi, Fabio
Abstract : Nowadays, the involvement of the microbiome in human health and many human diseases, including that strictly related to the scalphas been brought to the light. Indeed, more recently, authors highlighted the presence of a significant microbial shift both in nonscarring (Androgenetic alopecia and Alopecia areata) and scarring Alopecias. The advent of novel technologies together with the effort of many scientists in the microbiome field could provide in the nearest future a clearest framework about the strict relationship between human healthiness and symbiotic microorganism resident on different ecosystem of our body. In this view, the use of Omics approaches has to be considered as no longer negligible when studying the microbiome implication in human health and disease.